Peran Dinas Koperasi dan Usaha Mikro dalam Pengembangan Usaha Mikro di Kabupaten Tulungagung pada Masa Pandemi - Margayaningsih, Dwi Iriani (Universitas Islam Balitar, 2023)
During this pandemic, micro-enterprises nationally, especially in Tulungagung Regency, did not develop rapidly. In situations like this, the role of the cooperative service is very decisive for MSMEs to continue to exist. In accordance with the objectives, the research used is qualitatively descriptive with interactive model analysis techniques, namely reducing data, presenting data and drawing conclusions. The results of the analysis identified nine roles for developing micro-enterprises in the Tulungagung area that were carried out well. MSME Entrepreneurs were able to add creativity to their products so that these products had their own added value. In the field of marketing and product development. MSME actors are assisted by the presence of PLUT (Integrated Business Service Center). While inhibiting factors such as sometimes development training participants are not in line with the expertise they have, lack of manpower for the MSME development and empowerment division, lack of maximum post-training coaching.